2020
DOI: 10.1364/boe.378506
|View full text |Cite
|
Sign up to set email alerts
|

Co-registered combined OCT and THz imaging to extract depth and refractive index of a tissue-equivalent test object

Abstract: Terahertz (THz) imaging and optical coherence tomography (OCT) provide complementary information with similar length scales. In addition to OCT's extensive use in ophthalmology, both methods have shown some promise for other medical applications and non-destructive testing. In this paper, we present an iterative algorithm that combines the information from OCT and THz imaging at two different measurement locations within an object to determine both the depth of the reflecting layers at the two locations and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Terahertz imaging can provide unique information about the absorption properties of fresh tissue, but often lacks information about the tissue structure. Like many other established medical imaging modalities, terahertz imaging can be combined with other techniques to elucidate more information, for example, Fan et al combined terahertz with polarised optical images to delineate margins of skin cancer [255], and Fitzgerald et al have shown that terahertz and optical coherence tomography can be combined to extract depth resolved properties of samples [256].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Terahertz imaging can provide unique information about the absorption properties of fresh tissue, but often lacks information about the tissue structure. Like many other established medical imaging modalities, terahertz imaging can be combined with other techniques to elucidate more information, for example, Fan et al combined terahertz with polarised optical images to delineate margins of skin cancer [255], and Fitzgerald et al have shown that terahertz and optical coherence tomography can be combined to extract depth resolved properties of samples [256].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…In this detection model, the color, intensity, and direction of saliency mapping can be calculated by the difference between adjacent pixels and multiscale center. en, the final saliency map is obtained by combining the above three feature maps [10][11][12]. Figure 1 demonstrates the specific algorithm steps.…”
Section: Improved Generative Adversarialmentioning
confidence: 99%
“…8. 150 In addition, efforts by Kitahara et al showed that FD THz OCT complements traditional TD OCT. Signal processing advances in the field allowed them to provide reliable tomographic measurements despite substantial noise levels in their broadband THz source. 151 In conclusion, the appropriate groundwork has been laid for efficient, robust, high-resolution THz OCT.…”
Section: Developments In Optical Coherence Tomographymentioning
confidence: 99%